Competitividad en las peque\~nas y medianas empresas del Distrito Metropolitano de Quito; Competitiveness in small and medium sized businesses in the Metropolitan District of Quito - Jaime Cadena Echeverriá; Mercedes Eugenia Aguilar; Pedro Enrique Buitron (Small Business International Review (SBIR), 2018)
Basado en el modelo de competitividad planteado por el World Economic Forum (WEF) se pretende analizar, conocer y comparar el nivel de competitividad en las PYMES de los sectores priorizados: Turismo, Alimentos, Textil, Farmaceútico, Metalmecańico, Confeccioń y Calzado en el Distrito Metropolitano de Quito, de manera descriptiva y no experimental; La informacioń se obtuvo a traveś del anaĺisis documental y encuestas. Para determinar el nivel de competitividad y conocer la realidad de las PYMES se realizoĺa caracterizacioń de los sectores, determinando la importancia de eśtos para la transformacioń de la matriz productiva. El ińdice de competitividad se obtiene con el caĺculo de tres subińdices, que estań formados por doce pilares, cada uno de ellos compuesto por variables establecidas seguń el sector analizado. Se plantea estrategias para mejorar la competitividad, alineadas al cambio de la matriz productiva, encaminadas hacia la transformacioń de materias primas a producto final que podriá ser exportado y, de esta manera, agregar valor en beneficio del sector industrial del Ecuador. Existe la posibilidad de realizar el estudio al resto de sectores priorizados y en todas las provincias del paiś. – – The present investigation analyzes, knows and compares the level of competitiveness in the Small and Medium Enterprises of the prioritized sectors in the change of the productive matrix: Tourism, Food, Textile, Pharmaceutical, Metalworking, Clothing and Footwear in the Metropolitan District of Quito. This study is based on the competitiveness model proposed by the World Economic Forum (WEF). The study is non-experimental descriptive. The methods to obtain the data were the documentary analysis and surveys to obtain the soft data required by the WEF method. To determine the level of competitiveness and know the reality of SMEs, the characterization of the sectors was carried out, determining the importance of these for the transformation of the productive matrix, the competitiveness index according to the methodology is obtained with the calculation of 3 sub-indices, which are formed by 12 pillars and each pillar composed of variables established according to the sector analyzed. From the research of the current situation of SMEs and the determination of the level of sectoral competitiveness strategies for the national industry, with the vision of achieving better levels of competitiveness, these strategies are alienated to the change of the productive matrix, to search so that Ecuador stops being a producer of only raw material and becomes an exporter of final products with added value, benefiting both the business sector and Ecuador. The research could be extended by including the remaining sectors and the left provinces from Ecuador.
Keywords: L25; 650; SMEs; competitiveness; productive matrix; DMQ; Pymes; competitividad; matriz productiva; DMQ